A motor-driven adjustable prosthetic socket operated using a mobile phone app: A technical note. (June 2019) - Sanders, Joan E; Garbini, Joseph L; McLean, Jake B; Hinrichs, Paul; Predmore, Travis J; Brzostowski, Jacob T; Redd, Christian B; Cagle, John C
Highlights: A motor-driven, cabled-panel, trans-tibial amputee adjustable socket was developed. The system achieved an absolute steady state cable length error< 0.036 mm. 4 of 16 participants preferred cable length step adjustments <4.75 mm. User-selected ranges of cable draw were as low as 24 mm and as high as 114 mm. 11 of 13 participants were comfortable making size adjustments during walking. Abstract: Sockets that allow incremental size adjustment during ambulation may help prosthesis users improve management of their changes in limb volume and the quality of their prosthetic fit. A platform system was developed that allowed people with trans-tibial limb loss to adjust the radial positions of socket panels during ambulation in small increments via a motor mounted beneath the socket. The motor altered the length of a cable running through the socket panels according to commands communicated from a mobile phone. A proportional–integral–derivative controller adjusted the voltage applied to the motor via pulse-width modulation to achieve target settings. Bench test results showed that when the system was subjected to loads comparable to those expected during clinical use, maximum absolute steady state error was 0.036 mm. Treadmill testing on 16 people with trans-tibial limb amputation demonstrated that the range of cable lengths over which participants deemed fit clinically acceptable varied between 24 mm and 114 mm depending on the user. In field testing 11 of 13 participants were comfortable making socket size adjustments while walking. The developed system achieves incremental socket size adjustments appropriate for research and development of ambulatory adjustable sockets.